Manchoukuo : - Kawakami, Kiyoshi Karl (The Macmillan company, 1933)
This latest volume the well-known Japanese correspondent reviews the Manchurian problem, making no bones about discussing the seamy sides and frankly facing the difficulties raised by recent developments.